Lepidozia bragginsiana, a new species from New Zealand (Marchantiopsida) - Cooper, Endymion D.; Renner, Matt A. M. (Phytotaxa, 2014)
Molecular and morphological data support the recognition of a new Lepidozia species related to L. pendulina and also endemic to New Zealand, which we dedicate to Dr John Braggins. Lepidozia bragginsiana can be distinguished from closely related and other similar species by its bipinnate branching, the narrow underleaf lobes, typically uniseriate toward their tip on both primary and secondary shoots, the asymmetric underleaves on primary shoots that are usually narrower than the stem and also possess basal spines and spurs, the production of spurs and spines, or even accessory lobes, on the postical margin of primary and secondary shoot leaves; and by the relatively small leaf cells with evenly thickened walls.  Lepidozia bragginsiana is an inhabitant of hyper-humid forest habitats where it occupies elevated microsites on the forest floor. A lectotype is proposed for L. obtusiloba.